Beaver Fever: Whole-Genome Characterization of Waterborne Outbreak and Sporadic Isolates To Study the Zoonotic Transmission of Giardiasis - Clement K.-M. Tsui (American Society for Microbiology, 2018)
ABSTRACT Giardia causes the diarrheal disease known as giardiasis; transmission through contaminated surface water is common. The protozoan parasite’s genetic diversity has major implications for human health and epidemiology. To determine the extent of transmission from wildlife through surface water, we performed whole-genome sequencing (WGS) to characterize 89 Giardia duodenalis isolates from both outbreak and sporadic infections: 29 isolates from raw surface water, 38 from humans, and 22 from veterinary sources. Using single nucleotide variants (SNVs), combined with epidemiological data, relationships contributing to zoonotic transmission were described. Two assemblages, A and B, were identified in surface water, human, and veterinary isolates. Mixes of zoonotic assemblages A and B were seen in all the community waterborne outbreaks in British Columbia (BC), Canada, studied. Assemblage A was further subdivided into assemblages A1 and A2 based on the genetic variation observed. The A1 assemblage was highly clonal; isolates of surface water, human, and veterinary origins from Canada, United States, and New Zealand clustered together with minor variation, consistent with this being a panglobal zoonotic lineage. In contrast, assemblage B isolates were variable and consisted of several clonal lineages relating to waterborne outbreaks and geographic locations. Most human infection isolates in waterborne outbreaks clustered with isolates from surface water and beavers implicated to be outbreak sources by public health. In-depth outbreak analysis demonstrated that beavers can act as amplification hosts for human infections and can act as sources of surface water contamination. It is also known that other wild and domesticated animals, as well as humans, can be sources of waterborne giardiasis. This study demonstrates the utility of WGS in furthering our understanding of Giardia transmission dynamics at the water-human-animal interface. IMPORTANCE Giardia duodenalis causes large numbers of gastrointestinal illness in humans. Its transmission through the contaminated surface water/wildlife intersect is significant, and the water-dwelling rodents beavers have been implicated as one important reservoir. To trace human infections to their source, we used genome techniques to characterize genetic relationships among 89 Giardia isolates from surface water, humans, and animals. Our study showed the presence of two previously described genetic assemblages, A and B, with mixed infections detected from isolates collected during outbreaks. Study findings also showed that while assemblage A could be divided into A1 and A2, A1 showed little genetic variation among animal and human hosts in isolates collected from across the globe. Assemblage B, the most common type found in the study surface water samples, was shown to be highly variable. Our study demonstrates that the beaver is a possible source of human infections from contaminated surface water, while acknowledging that theirs is only one role in the complex cycle of zoonotic spread. Mixes of parasite groups have been detected in waterborne outbreaks. More information on Giardia diversity and its evolution using genomics will further the understanding of the epidemiology of spread of this disease-causing protozoan.